Lineaments and their association with landslide occurrences along the Ranau-Tambunan road, Sabah - Norbert Simon, Rodeano Roslee, Nightingle Lian Marto, Juhari Mat, . (2014)
The purpose of this study is to assess the influence of lineaments on landslide occurrences based on the concept of lineament density. The Ranau-Tambunan districts with a 54 km road stretch from Ranau to Tambunan, crossing the Crocker and Trusmadi Formations is selected as the study area. In total, the study area is 844.7 km2. Both formations have similar area with Crocker at 405.5 km2 and Trusmadi at 425.6 km2 The rest are either igneous and alluvium (13.6 km2).